Faith, Reason and Peace in Lessing's Late Works. Issue 159 (1st July 2019) - Moir, Cat
Abstract : This article argues that G. E. Lessing should be viewed as one of the German Enlightenment's foremost thinkers of peace alongside his contemporary Immanuel Kant, whose contribution to thinking peace in the eighteenth century is already well recognised. It makes this case by examining two of Lessing's late works: the 1779 drama Nathan the Wise and the 1780 essay The Education of the Human Race. The dialogue between faith and reason characteristic of Enlightenment discourse is at the heart of both texts, but here it is argued that peace is a crucial third moment. While in Nathan Lessing asserts the need to find peace between the forces of faith and reason in a literary register, in the Education essay he does so in a more explicitly theoretical mode.